2019
DOI: 10.1039/c9ta01979k
|View full text |Cite
|
Sign up to set email alerts
|

Supported molten-salt membranes for carbon dioxide permeation

Abstract: First review of supported molten-salt membranes highlighting materials challenges, mechanistic development and manufacturing opportunities towards energy applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 148 publications
0
29
0
Order By: Relevance
“…Dual-phase membranes offer outstanding CO 2 /N 2 selectivity (41000) as the solubility of CO 2 in molten carbonate is B10 4 higher than N 2 . 38,52 As N 2 is only detected on the permeate side of a dual-phase membrane as the result of a leak, selectivity is routinely calculated based on solubilities alone. Here, we have adopted a more conservative approach and calculated a minimum selectivity based on the limit of detection of our analytical apparatus (Experimental methods text, ESI †).…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Dual-phase membranes offer outstanding CO 2 /N 2 selectivity (41000) as the solubility of CO 2 in molten carbonate is B10 4 higher than N 2 . 38,52 As N 2 is only detected on the permeate side of a dual-phase membrane as the result of a leak, selectivity is routinely calculated based on solubilities alone. Here, we have adopted a more conservative approach and calculated a minimum selectivity based on the limit of detection of our analytical apparatus (Experimental methods text, ESI †).…”
Section: Papermentioning
confidence: 99%
“…For a more detailed discussion of mechanistic concerns, the reader is referred to a recent review article on this class of membrane. 38 Regardless, ceramic-carbonate membranes and metal-carbonate membranes are most applicable to pre-and post-combustion CO 2 capture, respectively, due to the requirement for O 2 in the latter case. The first reported metal-carbonate membranes were fabricated from porous stainless-steel infiltrated with MC, 30 with CO 2 and O 2 fluxes stabilising at a level lower than that predicted by reaction (2).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known from CO2 transport membranes that the immobilization of the molten alkali metal carbonate phases strongly depends on the microstructure of the host structure (here: CaO) and the physical properties of the molten carbonates, e.g. the wettability [333]. Capillary forces, which decrease with increasing pore diameter, need to be high to withhold the molten alkali metal carbonates, and so sintering is expected to contribute to the loss of the alkali metals [334].…”
Section: Alkali Metal Dopingmentioning
confidence: 99%
“…Triviño et al [597] showed that the immobilization of eutectic salts within the sorbent can be achieved through core-shell MgO fibers. Valuable lessons may be learned also from high temperature CO2-conducting membranes, where the molten carbonate needs to be retained within the porous solid matrix [333], [598]- [601].…”
Section: Future Development Of Sorbents On the Lab Scalementioning
confidence: 99%
“…Fe is also known to decrease the densification temperature of the SDC system [19,20] by inducing viscous flow sintering [21]. Use of sacrificial materials, e.g., NiO template [16], allows for control of the pore volume, size, connectivity, and tortuosity, having a strong influence on the CO 2 permeability [22]. Other studies relied on the use of MgO as a sustainable, safer and cheaper alternative to metal-containing templates as a hard template for Ag–CGO porous cermets for solid oxide fuel cells [23].…”
Section: Introductionmentioning
confidence: 99%